Effectiveness of Lecture and Vaccination Centre Visit for Teaching Basics of Immunisation and Cold Chain to Students of Traditional Medicine in Kolkata: A Quasi-Experimental Study (Journal of Nobel Medical College, 2025)
Background: Immunization and cold chain management are integral to public health. Though traditional medicine curriculum includes these topics, students often lack practical exposure. This study evaluates the impact of lecture combined with vaccination center visit on knowledge of immunization and cold chain management among these students.Materials and Methods: A longitudinal, quasi-experimental study was conducted on traditional medicine students visiting the tertiary care hospital in Kolkata from June to December 2024. The intervention includedtwo-hour lecture followed by two-hour vaccination center visit. Knowledge assessments were conducted pre-intervention, post-intervention, and after one-month using a 20-item e-questionnaire on Vaccination &Adverse Event Following Immunisation, Cold Chain and Biomedical Waste Management.Comparisons between pre-test, post-test, and post-1-month test scores were conducted using Friedman test.Results: Among the 80 participantscompleting the study, median scores across all domains improved significantly (Friedman test p